Effective resumes and job applications [ (Learning Seed, 2000)
Shows job seekers the basics of preparing a resume (content, arrangement, style and tips for electronic resumes), composing correspondence accompanying the resume (use of names and titles, attention-getting phrases) and completing application forms (terminology to use, errors to avoid).